PENGEMBANGAN BAHAN AJAR GEOGRAFI SMA/MA KELAS X PADA MATERI PERAIRAN LAUT DENGAN MODEL DICK AND CAREY - Onik Farida Ni’matullah (Geography Education Study Program, Universitas Kanjuruhan Malang, 2017)
Product of the book developed is based on the scientific rule of geography content standard and the ruleof book writing through modification of Dick and Cary Model (2001). Procedures of development for this model consist of ten step but in this case,only five step were done. They are: 1) identifying competence standard, basic competence and indicator based on the concept BSNP, 2) analyzing the learning material, 3) improving and writing text books, 4) validating text books, 5) revising the final product of text book development. Based on the result of validation on material expert, text book is in good category (67%). The result of validation on learning design, text book is in good category (69%). The result of test on the students, text book is in very good category (75%). While the result of test on teacher, text book is in very good category (82%).